Polycarbonate polyester composition, molding compound and molding having excellent impact strength and high heat load capacity
Patent Information
- Application Number
- JP2023547571
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-02-08
- Filing Date
- 2022-02-01
- Publication Date
- 2025-02-10
- Estimated Expiration
- 2042-02-01
AI Technical Summary
Existing polycarbonate-polyester compositions experience undesired transesterification reactions during melt compounding and processing, leading to reduced heat deformation resistance, resilience, and altered crystallization behavior, which compromises the quality of molded articles.
A composition comprising polycarbonate, polyester, phosphorous acid, phosphonite, and sterically hindered phenol, optionally with mineral fillers and other additives, is formulated to stabilize the mixture and maintain high transition temperatures and impact strength.
The composition exhibits minimal reduction in heat deformation resistance and maintains high transition temperatures, ensuring good phase separation and improved impact strength even under unfavorable processing conditions.
Smart Images

Figure 2022167395000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition based on polycarbonates and polyesters for producing thermoplastic molding compounds, to the molding compounds as such, to the use of the composition or the molding compounds for producing moldings, and to the moldings as such. [Background technology]
[0002] Thermoplastic molding compounds containing polycarbonates and / or polyester carbonates and polyesters have been known for many years.
[0003] They are used in components in a wide range of industrial sectors, especially in the automotive industry. By varying the type and amount of the constituents and adding further additives and polymer compounding partners, the property profile can be widely adapted to the requirements of the respective application.
[0004] For many such applications, the components made from the molding compounds must be able to withstand relatively high temperatures and also possess excellent mechanical properties, such as high resilience under impact stress.
[0005] During the preparation of polycarbonate-polyester molding compounds during melt compounding and / or during processing of the molding compounds, for example during injection molding, undesirable transesterification reactions often occur between the polycarbonate and the polyester, particularly under unfavorable conditions, such as high temperatures, long residence times, and high mechanical stresses during melt compounding or injection molding.
[0006] This can impair important properties, for example the heat distortion resistance or resilience of the moulded body can be reduced. In addition, morphological properties can change, i.e. the crystallization and melting behaviour of the polyester can be disturbed and the glass transition temperature of the polycarbonate can be shifted to lower values. However, rapid crystallization has a positive effect on the demolding behaviour during injection moulding processes, so that cycle times are reduced and component production is more efficient. Undisturbed crystallization is also advantageous in terms of resistance to aggressive media.
[0007] It is therefore desirable to provide stabilizing additives to molding compounds composed of polycarbonates and polyesters. There are numerous documents on this subject in the prior art.
[0008] US Pat. No. 5,399,633 discloses polycarbonate-polyester compositions stabilized against yellowing with phosphorus-based acids.
[0009] US Pat. No. 5,399,633 discloses blends of polycarbonate and polyester protected against discoloration with phosphorus compounds.
[0010] US Pat. No. 5,399,633 discloses sterically hindered esters of phosphorous acid as stabilizers for polycarbonate-polyalkylene terephthalate compositions.
[0011] US Pat. No. 5,399,633 discloses a composition comprising polycarbonate, polyalkylene terephthalate, a mineral filler, and phosphorous acid as a stabilizer.
[0012] US Pat. No. 5,399,633 discloses a composition consisting of a mixture of polytetramethylene terephthalate, bisphenol A polycarbonate, and selected phosphorus compounds, characterized by excellent mechanical properties.
[0013] US Patent No. 5,399,633 discloses polycarbonate compositions stabilized against thermal degradation by using small amounts of phosphites as stabilizers, which can be either diaryl hydrogen phosphites, dialkyl hydrogen phosphites, or alkylaryl hydrogen phosphites, or mixtures thereof.
[0014] US Pat. No. 5,399,633 discloses blends of two polyesters which may also include a polycarbonate, the melt viscosity of which can be stabilized using certain phosphorus-containing additives.
[0015] US Patent No. 5,399,633 discloses that thermoplastic compositions comprised of polyester and / or polycarbonate resins, acrylic core-shell impact modifiers, and stabilizer packages are provided by an improved process in which the impact modifier and stabilizer components are first premixed and then the premix is mixed with the polyester and / or polycarbonate. The resulting blended compositions retain excellent properties without the need for large amounts of stabilizers.
[0016] US Pat. No. 5,399,633 discloses a composition comprising polybutylene terephthalate or polyethylene terephthalate or a mixture of polybutylene terephthalate and polyethylene terephthalate, polycarbonate, an inorganic filler, a stabilizer, and optionally a styrene rubber impact modifier. [Prior art documents] [Patent documents]
[0017] [Patent Document 1] International Publication No. 85 / 02622 [Patent Document 2] DE 2414849 [Patent Document 3] European Patent Application Publication No. 0417421 [Patent Document 4] European Patent Application Publication No. 3608358 [Patent Document 5] U.S. Patent No. 4,088,709 [Patent Document 6] DE 2402367 [Patent Document 7] European Patent Application Publication No. 0604074 [Patent Document 8] European Patent Application Publication No. 0114288 [Patent Document 9] European Patent Application Publication No. 0604080 Summary of the Invention [Problem to be solved by the invention]
[0018] Although the stabilization of polycarbonate / polyester compositions has been well documented, there remains a need for improvement.
[0019] It was desirable to provide a composition for producing thermoplastic molding compounds which is suitable for producing moldings having improved impact strength.
[0020] Furthermore, it was desirable that the heat distortion resistance of the shaped bodies should only be reduced slightly, even if the shaped bodies were produced under unfavourable processing conditions, such as at very high temperatures and / or very long residence times. The aim is therefore to ensure that the heat distortion resistance is only minimally affected by the processing conditions, thereby improving the reproducibility of this property.
[0021] It was also desirable that the transition temperatures mentioned above, i.e., the crystallization temperature of the polyester, the melting point of the polyester, and the glass transition temperature of the polycarbonate, be as high as possible so that good phase separation would be achieved. [Means for solving the problem]
[0022] Surprisingly, the following components: A) at least one polymer selected from the group consisting of polycarbonates and polyester carbonates; B) at least one polyester; C) phosphorous acid; D) at least one phosphonite; E) at least one sterically hindered phenol; It has now been found that the desired properties are exhibited by a composition for producing a thermoplastic molding compound, comprising or consisting of:
[0023] The composition optionally comprises, as component F, at least one mineral filler based on talc, and, as component G, optionally also comprises at least one additive selected from the group consisting of lubricants and release agents, flame retardants, flame retardant synergists, conductive additives, UV / light protection agents, nucleating agents, hydrolysis protection agents, scratch resistance improving additives, IR absorbers, optical brighteners, fluorescent additives, impact modifiers, dyes and pigments, and fillers and reinforcing agents other than component F. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] In a preferred embodiment, the composition comprises: 40% by weight to 80% by weight, more preferably 45% by weight to 75% by weight, particularly preferably 50% by weight to 66% by weight of component A; 15% by weight to 45% by weight, more preferably 18% by weight to 40% by weight, particularly preferably 20% by weight to 35% by weight of component B; 0.005% by weight to 0.1% by weight, more preferably 0.008% by weight to 0.06% by weight, particularly preferably 0.01% by weight to 0.05% by weight of component C; 0.05% by weight to 1% by weight, more preferably 0.08% by weight to 0.8% by weight, and particularly preferably 0.1% by weight to 0.3% by weight of component D; 0.05% by weight to 1% by weight, more preferably 0.08% by weight to 0.8% by weight, and particularly preferably 0.1% by weight to 0.3% by weight of component E; 0% to 25% by weight, more preferably 0% to 20% by weight, particularly preferably 5% to 20% by weight of component F; 0% to 20% by weight, more preferably 0.1% to 15% by weight, and particularly preferably 0.2% to 10% by weight of component G; Includes.
[0025] Unless otherwise stated, all weight percentages are of the total composition.
[0026] In a preferred embodiment, the composition consists of Components A to G at about 90% by weight, more preferably at about 95% by weight, and particularly preferably at about 100% by weight.
[0027] The above mentioned preferred individual ranges and preferred embodiments of the different components can be freely combined with one another.
[0028] Ingredient A According to the invention, suitable component A aromatic polycarbonates and / or aromatic polyestercarbonates are known from the literature or can be prepared by methods known from the literature (for the preparation of aromatic polycarbonates, see, for example, Schnell, "Chemistry and Physics of Polycarbonates", Interscience Publishers, 1964, and also DE-A-1 495 626, DE-A-2 232 877, DE-A-2 703 376, DE-A-2 714 544, DE-A-3 000 610, DE-A-3 832 396; for the preparation of aromatic polyestercarbonates, see, for example, DE-A-3 007 934).
[0029] Aromatic polycarbonates are prepared, for example, by reacting diphenols with carbonyl halides, preferably phosgene and / or aromatic dicarbonyl dihalides, preferably dihalides of benzenedicarboxylic acids, by interfacial methods, optionally using chain terminators, such as monophenols, and optionally using trifunctional or higher branching agents, such as triphenols or tetraphenols. Preparation via melt polymerization methods by reacting diphenols with, for example, diphenyl carbonate is also possible.
[0030] The diphenols for the preparation of the aromatic polycarbonates and / or aromatic polyester carbonates preferably have the formula (1): [ka] (In the formula, A is a single bond, C1-C5-alkylene, C2-C5-alkylidene, C5-C6-cycloalkylidene, -O-, -SO-, -CO-, -S-, -SO2-, C6-C6-alkylene optionally condensed with a further aromatic ring containing a heteroatom. 12 -arylene, or formula (2) or formula (3): [ka] Based on B is, in each case, C1 to C 12 - alkyl, preferably methyl, halogen, preferably chlorine and / or bromine, Each x is independently 0, 1, or 2; p is 1 or 0, and R 5 and R 6 For each X 1 are individually selectable, each independently being hydrogen or C1-C6-alkyl, preferably hydrogen, methyl, or ethyl; X 1 is carbon, and m is an integer from 4 to 7, preferably 4 or 5, provided that at least one atom X 1 R on top 5 and R 6 is a diphenol of the formula (I is alkyl at the same time).
[0031] Preferred diphenols are hydroquinone, resorcinol, dihydroxydiphenols, bis(hydroxyphenyl)-C1-C5-alkanes, bis(hydroxyphenyl)-C5-C6-cycloalkanes, bis(hydroxyphenyl)ethers, bis(hydroxyphenyl)sulfoxides, bis(hydroxyphenyl)ketones, bis(hydroxyphenyl)sulfones, and α,α-bis(hydroxyphenyl)diisopropylbenzene, and their ring brominated and / or ring chlorinated derivatives.
[0032] Particularly preferred diphenols are 4,4'-dihydroxybiphenyl, bisphenol A, 2,4-bis(4-hydroxyphenyl)-2-methylbutane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-dihydroxydiphenyl sulfide, 4,4'-dihydroxydiphenyl sulfone, and their dibrominated or dichlorinated and tetrabrominated or tetrachlorinated derivatives, such as 2,2-bis(3-chloro-4-hydroxyphenyl)propane, 2,2-bis(3,5-dichloro-4-hydroxyphenyl)propane, or 2,2-bis(3,5-dibromo-4-hydroxyphenyl)propane. 2,2-bis(4-hydroxyphenyl)propane (bisphenol A) is particularly preferred.
[0033] The diphenols may be used individually or in the form of any desired mixtures. The diphenols are known from the literature or are obtainable by methods from the literature.
[0034] Examples of chain terminators suitable for the preparation of thermoplastic aromatic polycarbonates include phenol, p-chlorophenol, p-tert-butylphenol or 2,4,6-tribromophenol, as well as long-chain alkylphenols, such as 4-[2-(2,4,4-trimethylpentyl)]phenol, 4-(1,3-tetramethylbutyl)phenol according to DE-A-2842005, and mono- or dialkylphenols having a total of 8 to 20 carbon atoms in the alkyl substituent, such as 3,5-di-tert-butylphenol, p-isooctylphenol, p-tert-octylphenol, p-dodecylphenol, as well as 2-(3,5-dimethylheptyl)phenol and 4-(3,5-dimethylheptyl)phenol. The amount of chain terminator used is generally between 0.5 mol% and 10 mol% relative to the total moles of the diphenols used in each case.
[0035] The thermoplastic aromatic polycarbonate has an average molecular weight (weight average M w , as measured by GPC (gel permeation chromatography) using bisphenol A based polycarbonate standards. The preferred ranges provide a particularly advantageous balance of mechanical and rheological properties in the compositions of the present invention.
[0036] The thermoplastic aromatic polycarbonates can be branched in a known manner, preferably by incorporating 0.05 mol % to 2.0 mol % of trifunctional or more than trifunctional compounds, for example compounds with three or more phenolic groups, relative to the total sum of the diphenols used. It is preferred to use linear polycarbonates, more preferably linear polycarbonates based on bisphenol A.
[0037] Both homopolycarbonates and copolycarbonates are suitable. The inventive copolycarbonates according to component A can also be prepared using polydiorganosiloxanes having 1% to 25% by weight, preferably 2.5% to 25% by weight, of hydroxyaryloxy end groups, based on the total amount of diphenols used. These are known (US Pat. No. 3,419,634) and can be prepared by methods known from the literature. Likewise suitable are polydiorganosiloxane-containing copolycarbonates, the preparation of which is described, for example, in DE-A-3334782.
[0038] The aromatic dicarbonyl dihalides for the preparation of aromatic polyester carbonates are preferably the diacyl dichlorides of isophthalic acid, terephthalic acid, diphenyl ether 4,4'-dicarboxylic acid, and naphthalene-2,6-dicarboxylic acid.
[0039] Particularly preferred are mixtures of the diacyl dichlorides of isophthalic and terephthalic acid in a ratio between 1:20 and 20:1.
[0040] In the preparation of polyester carbonates, a carbonyl halide, preferably phosgene, is additionally used in combination as a difunctional acid derivative.
[0041] In addition to the monophenols already mentioned, chain terminators for the preparation of aromatic polyester carbonates include these chlorocarbonates and, optionally, C1-C 22 - Acid chlorides of aromatic monocarboxylic acids which may be substituted with alkyl groups or halogen atoms, and aliphatic C2-C 22 Monocarboxylic acid chlorides are also included.
[0042] The amount of chain terminator is in each case 0.1 mol % to 10 mol % relative to the number of moles of diphenols in the case of phenolic chain terminators and relative to the number of moles of dicarboxylic acid dichlorides in the case of monocarboxylic acid chloride chain terminators.
[0043] One or more aromatic hydroxycarboxylic acids may also be used in the preparation of the aromatic polyester carbonates.
[0044] The aromatic polyestercarbonates can be linear or branched, as is known (see DE-A-2 940 024 and DE-A-3 007 934), but linear polyestercarbonates are preferred here.
[0045] Branching agents which may be used are, for example, tri- or polyfunctional carbonyl chlorides, such as trimesoyl trichloride, cyanuroyl trichloride, 3,3',4,4'-benzophenone tetracarbonyl tetrachloride, 1,4,5,8-naphthalene tetracarbonyl tetrachloride or pyromellitoyl tetrachloride, in an amount of 0.01 mol % to 1.0 mol % (relative to the dicarbonyl dichloride used), or tri- or polyfunctional phenols, such as phloroglucinol, 4,6-dimethyl-2,4,6-tri(4-hydroxyphenyl)hept-2-ene ... The branching agents are 1,3,5-tri(4-hydroxyphenyl)heptane, 1,3,5-tri(4-hydroxyphenyl)benzene, 1,1,1-tri(4-hydroxyphenyl)ethane, tri(4-hydroxyphenyl)phenylmethane, 2,2-bis[4,4-bis(4-hydroxyphenyl)cyclohexyl]propane, 2,4-bis(4-hydroxyphenylisopropyl)phenol, tetra(4-hydroxyphenyl)methane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methylphenol, 2-(4-hydroxyphenyl)-2-(2,4-dihydroxyphenyl)propane, tetra(4-[4-hydroxyphenylisopropyl]phenoxy)methane, and 1,4-bis[4,4'-dihydroxytriphenyl)methyl]benzene. Phenol-based branching agents can be initially charged with the diphenols, and acid chloride branching agents can be introduced with the acid dichlorides.
[0046] The proportion of carbonate structural units in the thermoplastic aromatic polyester carbonate can be varied as desired.Preferably, the proportion of carbonate groups is at most 100 mol%, particularly at most 80 mol%, more preferably at most 50 mol%, based on the total sum of ester groups and carbonate groups.The ester moieties of the aromatic polyester carbonate and also its carbonate moieties can be in the form of blocks or have a random distribution in the polycondensate.
[0047] The thermoplastic aromatic polycarbonates and polyester carbonates may be used alone or in any desired mixture.
[0048] As component A it is preferred to use polycarbonates based on bisphenol A.
[0049] The proportion of component A in the composition is preferably 40% by weight to 80% by weight, more preferably 45% by weight to 75% by weight, and particularly preferably 50% by weight to 66% by weight.
[0050] Component B According to the invention, a polyester or a mixture of polyesters is used as component B.
[0051] The polyesters may be the reaction product of aromatic, aliphatic, or cycloaliphatic dicarboxylic acids and aliphatic, cycloaliphatic, or araliphatic diols.
[0052] Diols that can be used in the preparation of the polyesters according to the invention include, for example, ethylene glycol, butane-1,4-diol, propane-1,3-diol, tetramethylcyclobutanediol, isosorbitol, 2-ethylpropane-1,3-diol, neopentyl glycol, pentane-1,5-diol, hexane-1,6-diol, cyclohexane-1,4-dimethanol, 3-ethylpentane-2,4-diol, 2-methylpentane-2,4-diol, 2,2,4-trimethylpentane-1,3-diol, 2-ethylhexane-1,3 -diols, 2,2-diethylpropane-1,3-diol, hexane-2,5-diol, 1,4-di(β-hydroxyethoxy)benzene, 2,2-bis(4-hydroxycyclohexyl)propane, 2,4-dihydroxy-1,1,3,3-tetramethylcyclobutane, 2,2-bis(4-β-hydroxyethoxyphenyl)propane and 2,2-bis(4-hydroxypropoxyphenyl)propane and mixtures thereof (DE-A-2 407 674, DE-A-2 407 776, DE-A-2 715 932).
[0053] As the alicyclic carboxylic acid, for example, cyclohexanedicarboxylic acid can be used. A suitable polyester derived from this acid contains cyclohexanedimethanol as a diol component and is called PCCD. The manufacturing process of such polyester is described, for example, in US Patent No. 6,455,564.
[0054] The polyester of component D is preferably a polyalkylene terephthalate.
[0055] In a preferred embodiment, these are reaction products of terephthalic acid or its reactive derivatives, such as the dimethyl ester or anhydride, with aliphatic, cycloaliphatic or araliphatic diols, and mixtures of these reaction products.
[0056] Thus, the polyalkylene terephthalates contain structural units derived from terephthalic acid and from an aliphatic, cycloaliphatic or araliphatic diol.
[0057] In the context of the present invention, polyalkylene terephthalates are to be understood as including polyesters which contain not only terephthalic acid groups, but also a proportion of further aromatic, aliphatic or cycloaliphatic dicarboxylic acids in an amount of up to 50 mol %, preferably up to 25 mol %. These can contain, for example, aromatic or cycloaliphatic dicarboxylic acids having 8 to 14 carbon atoms, or aliphatic dicarboxylic acids having 4 to 12 carbon atoms, such as phthalic acid, isophthalic acid, naphthalene-2,6-dicarboxylic acid, 4,4'-biphenyldicarboxylic acid, succinic acid, adipic acid and cyclohexanedicarboxylic acid.
[0058] It is preferred to use only terephthalic acid and isophthalic acid.
[0059] Diols that can be used in the production of the polyalkylene terephthalate according to the present invention include, for example, ethylene glycol, butane-1,4-diol, propane-1,3-diol, tetramethylcyclobutanediol, isosorbitol, 2-ethylpropane-1,3-diol, neopentyl glycol, pentane-1,5-diol, hexane-1,6-diol, cyclohexane-1,4-dimethanol, 3-ethylpentane-2,4-diol, 2-methylpentane-2,4-diol, 2,2,4-trimethylpentane-1,3-diol, 2-ethylhexane These include 1,3-diol, 2,2-diethylpropane-1,3-diol, hexane-2,5-diol, 1,4-di(β-hydroxyethoxy)benzene, 2,2-bis(4-hydroxycyclohexyl)propane, 2,4-dihydroxy-1,1,3,3-tetramethylcyclobutane, 2,2-bis(4-β-hydroxyethoxyphenyl)propane and 2,2-bis(4-hydroxypropoxyphenyl)propane and mixtures thereof (DE-A-2 407 674, DE-A-2 407 776, DE-A-2 715 932).
[0060] Common names for these polyalkylene terephthalates are for example PET, PBT, PETG, PCTG, PEICT, PCT or PTT.
[0061] Preferred polyalkylene terephthalates contain at least 80% by weight, preferably at least 90% by weight, of the dicarboxylic acid component of terephthalic acid groups and at least 80% by weight, preferably at least 90% by weight, of the diol component of ethylene glycol groups and / or butane-1,4-diol groups.
[0062] In a preferred embodiment, polyalkylene terephthalates prepared exclusively from terephthalic acid and its reactive derivatives (such as its dialkyl esters) and ethylene glycol and / or butane-1,4-diol, as well as mixtures of these polyalkylene terephthalates, are used as component B.
[0063] The polyalkylene terephthalates may be branched by incorporating relatively small amounts of tri- or tetrahydric alcohols or tri- or tetrabasic carboxylic acids, for example according to DE-A-1 900 270 and US-A-3 692 744. Examples of preferred branching agents are trimesic acid, trimellitic acid, trimethylolethane and trimethylolpropane, and pentaerythritol.
[0064] Particularly preferred are polyalkylene terephthalates prepared exclusively from terephthalic acid and its reactive derivatives (eg, dialkyl esters thereof) and ethylene glycol and / or butane-1,4-diol, as well as mixtures of these polyalkylene terephthalates.
[0065] In a particularly preferred embodiment, polyethylene terephthalate, polybutylene terephthalate or a mixture of these polyesters is used as component B. The use of polyethylene terephthalate is most preferred.
[0066] The polyalkylene terephthalates preferably used have an intrinsic viscosity of preferably 0.52 dl / g to 0.95 dl / g, particularly preferably 0.56 dl / g to 0.80 dl / g and very particularly preferably 0.58 dl / g to 0.68 dl / g. To determine the intrinsic viscosity, the specific viscosity is first measured in dichloroacetic acid at 25° C. and a concentration of 1% by weight in accordance with DIN 53728-3 in an Ubbelohde viscometer.
[0067] The determined intrinsic viscosity is then calculated from the measured specific viscosity x 0.0006907 + 0.063096 (x indicates multiplication).
[0068] Polyalkylene terephthalates having a preferred intrinsic viscosity provide an advantageous balance of mechanical and rheological properties in the compositions according to the invention.
[0069] Polyalkylene terephthalates can be prepared by known methods (see, for example, Kunststoff-Handbuch, volume VIII, p. 695 ff, Carl-Hanser-Verlag, Munich 1973).
[0070] The proportion of component B in the composition is preferably 15% by weight to 45% by weight, more preferably 18% by weight to 40% by weight, and particularly preferably 20% by weight to 35% by weight.
[0071] Component C As component C, the composition contains phosphorous acid, H3PO3.
[0072] Another term is phosphonic acid. In the following, only the term phosphorous acid will be used.
[0073] Phosphorous acid can be used as solid or as aqueous solution. It is preferred to use as solid. In the composition according to the present invention, this improves the stability of the polymeric components used during compounding, and therefore improves the mechanical properties of the composition.In addition, it is easier to meter into compounding unit than using aqueous acid solution, and the risk of possible corrosion of machine parts is also significantly reduced.
[0074] Component C can also be used in this form bound to an organic or inorganic adsorbent or absorbent, for example by mixing component C with the adsorbent or absorbent to form a free-flowing powder prior to compounding of the composition. These absorbents or adsorbents are preferably finely divided and / or porous materials with a large external and / or internal surface area.
[0075] These materials are preferably thermally inert inorganic materials, such as metal or transition metal oxides or mixed oxides, silicates, silicas, sulfides, nitrides, etc. In a particularly preferred embodiment, they are finely divided and / or microporous silicas or silicon oxides or silicates of natural or synthetic origin.
[0076] It is also possible to use phosphorous acid in the form of a masterbatch based on polycarbonate or polyester. The term masterbatch should be understood to mean that phosphorous acid is premixed with a thermoplastic (polycarbonate or polyester) in an amount greater than the intended use concentration in the composition. This mixture is then added to the composition in an appropriate amount to achieve the desired acid concentration in the composition.
[0077] The proportion of component C in the composition is preferably 0.005% by weight to 0.1% by weight, more preferably 0.008% by weight to 0.06% by weight, and particularly preferably 0.01% by weight to 0.05% by weight.
[0078] Component D The composition comprises a phosphonite as component D. Mixtures of two or more such components can also be used.
[0079] Phosphonites are derived from the phosphonous acid HP(OH)2 and have the following general structure (4): [ka] (In the formula, n is 1, 2, 3, or 4; R1, R2 and R3 are each independently C1 to C 60 -Alkyl, C6-C 12 -Aryl and C5-C 12 cycloalkyl and hydrogen, where the specified groups can in each case be substituted by aryl, alkyl, aryloxy, alkyloxy, heteroatoms and / or heterocycles, where R2 and R3 cannot simultaneously be hydrogen.
[0080] The groups are preferably substituted by C1-C8-alkyl, branched C1-C8-alkyl or cumyl, where the substituents may be the same or different.
[0081] If the radicals are aryl groups, these are preferably substituted in positions 2 and 4, or positions 2, 4 and 6. Tert-butyl substituents in these positions are very particularly preferred.
[0082] The phosphonites may be mononuclear (n=1) or polynuclear (n=2, 3 or 4), aliphatic, alicyclic and / or aromatic substituted phosphonites.
[0083] A "polynuclear" phosphonite is understood to mean one which contains two or more phosphonite groups in one molecule, i.e. a phosphorus atom which is organically substituted at one position and which bears two further organically substituted oxygen atoms.
[0084] Another name for structure (4) is "hypophosphite" or even "phosphite".
[0085] Particularly preferred is the structure (5): [ka] is used as component D.
[0086] In component D), in addition to structure (5), other isomeric structures may also be present, with structure (5) being the main component.
[0087] Compound (5) is classified as CAS: 119345-01-6 and is commercially available from BASF (Germany) under the name Irgafos™ P-EPQ.
[0088] The proportion of component D in the composition is preferably 0.05% by weight to 1% by weight, more preferably 0.08% by weight to 0.8% by weight, and particularly preferably 0.1% by weight to 0.3% by weight.
[0089] Component E The composition comprises a sterically hindered phenol as component E. Mixtures of two or more such components may also be used.
[0090] General structure (6a) or (6b): [ka] (wherein n is 1, 2, 3, or 4; R1, R2, and R3 are each independently C1-C4 alkyl or hydrogen; X is a direct bond or a C1-C 60 which may contain oxygen and / or nitrogen; R4 is a direct bond, carbon, C1-C8-alkyl, aryl, or a group represented by formula (7a), (7b) or (7c): [ka] Particularly preferred is a compound of the formula:
[0091] Component E particularly preferably has the structures (8) and (9): [ka] The compound is selected from at least one of the following compounds:
[0092] Compound (8) is classified as CAS: 6683-19-8 and is commercially available under the name Irganox™ 1010 from BASF (Germany).
[0093] Compound (9) is classified as CAS: 2082-79-3 and is commercially available from BASF (Germany) under the name Irganox™ 1076.
[0094] The proportion of component E in the composition is preferably 0.05% by weight to 1% by weight, more preferably 0.08% by weight to 0.8% by weight, and particularly preferably 0.1% by weight to 0.3% by weight.
[0095] Component F As component F, the thermoplastic molding compound may optionally contain at least one mineral filler based on talc as reinforcing agent.
[0096] In a preferred embodiment, the talc-based mineral filler is the only reinforcing agent.
[0097] Suitable as talc-based mineral fillers in the context of the present invention are any particulate fillers that a person skilled in the art would associate with talc or talcum. Also suitable are all particulate fillers that are commercially available and contain the term talc or talcum as a characteristic feature in their product description.
[0098] Preference is given to mineral fillers which have a talc content according to DIN 55920 of more than 50% by weight, preferably more than 80% by weight, particularly preferably more than 95% by weight and very particularly preferably more than 98% by weight, based on the total mass of the filler.
[0099] Talc should be understood to mean naturally occurring or synthetically produced talc.
[0100] Pure talc has a chemical composition of 3MgO·4SiO2·H2O, and therefore in each case for talc, a MgO content of 31.9% by weight, a SiO2 content of 63.4% by weight, and a chemically bound water content of 4.8% by weight. It is a silicate with a layered structure.
[0101] Naturally occurring talc materials generally do not have the above ideal composition because they are contaminated, for example, by partial substitution of magnesium by other elements, by partial substitution of silicon by aluminum, and / or by intergrowth with other minerals such as dolomite, magnesite and chlorite.
[0102] The talc grades which are particularly preferably used as component F are characterized by a particularly high purity, in each case by an MgO content of 28% to 35% by weight, preferably 30% to 33% by weight and particularly preferably 30.5% to 32% by weight, and by an SiO content of 55% to 65% by weight, preferably 58% to 64% by weight and particularly preferably 60% to 62.5% by weight, based on the talc.
[0103] Particularly preferred types of talc are also characterized by an Al2O3 content of less than 5% by weight, particularly preferably less than 1% by weight and in particular less than 0.7% by weight, in each case based on the talc.
[0104] Also advantageous and therefore preferred are those having an average particle size d of 0.1 μm to 20 μm, preferably 0.2 μm to 10 μm, more preferably 0.5 μm to 5 μm, even more preferably 0.7 μm to 2.5 μm, and particularly preferably 1.0 μm to 2.0 μm. 50 The use of talc according to the invention in the form of a finely divided grade having
[0105] The talc-based mineral fillers for use according to the invention preferably have an upper particle size or grain size d o of less than 10 μm, preferably less than 7 μm, particularly preferably less than 6 μm, and especially preferably less than 4.5 μm. 95 The filler has 95 Value and d 50 Values are determined by SEDIGRAPH D5000 sedimentation analysis according to ISO 13317-3.
[0106] The talc-based mineral fillers may optionally be surface-treated to achieve better bonding with the polymer matrix: they may be provided with, for example, an adhesion promoter system based on functionalized silanes.
[0107] The average aspect ratio (diameter to thickness) of the particulate filler, determined by electron micrographs of ultrathin sections of the finished product and by measuring a representative amount of filler particles (approximately 50 particles), is preferably in the range of 1 to 100, particularly preferably 2 to 25, and especially preferably 5 to 25.
[0108] As a result of processing to obtain the molding compound / body, the particulate filler may have a smaller d in the molding compound / body than the filler originally used. 95 / d 50 may have the following structure:
[0109] The proportion of component F in the composition is preferably 0% by weight to 25% by weight, more preferably 0% by weight to 20% by weight, and particularly preferably 5% by weight to 20% by weight.
[0110] Ingredient G The composition may include, as component G, a commercially available polymeric additive.
[0111] Commercially available polymer additives of component E include, for example, internal and external lubricants and release agents (e.g. pentaerythritol tetrastearate, montan wax or polyethylene wax), flame retardants, flame retardant synergists, conductive additives (e.g. conductive carbon black or carbon nanotubes), UV / light protection agents, nucleating agents (e.g. sodium phenylphosphinate, aluminum oxide, silicon dioxide, salts of aromatic carboxylic acids), hydrolysis protection agents, scratch resistance improving additives (e.g. silicone oils), IR absorbers, optical brighteners, fluorescent additives, impact modifiers (with or without core-shell structure), further polymer compounding partners, as well as additives such as dyes and pigments (e.g. titanium dioxide, ultramarine blue, iron oxide, carbon black, phthalocyanines, quinacridones, perylenes, nigrosine and anthraquinones), and fillers and reinforcing agents (different from component F), or mixtures of several of the additives mentioned.
[0112] Further reinforcing agents are preferably selected from the group consisting of mica, silicates, quartz, titanium dioxide, kaolin, amorphous silica, magnesium carbonate, chalk, feldspar, barium sulfate, glass spheres, ceramic spheres, wollastonite and glass fibres.
[0113] The composition according to the invention preferably contains at least one mold release agent, preferably pentaerythritol tetrastearate.
[0114] In a preferred embodiment, the composition comprises, as component G, at least one additive selected from the group comprising lubricants and release agents, UV / light protection agents, antistatic agents, dyes, pigments and fillers and reinforcing agents (different from component F).
[0115] The additives can be used alone or in admixture / masterbatch form.
[0116] In a preferred embodiment, the composition does not contain any other fillers or reinforcing agents other than component F.
[0117] In a preferred embodiment, the composition does not include a rubber modified graft polymer.
[0118] In a preferred embodiment, the composition does not comprise a vinyl (co)polymer, in particular SAN (styrene-acrylonitrile).
[0119] In a preferred embodiment, the composition is free of phosphorus-based flame retardants.
[0120] Free of an ingredient should be understood to mean that less than 0.5% by weight, preferably less than 0.1% by weight, especially preferred 0% by weight of this ingredient is present in the composition.
[0121] The proportion of component G in the composition is preferably 0 to 20% by weight, more preferably 0.1 to 15% by weight, and particularly preferably 0.2 to 10% by weight.
[0122] Manufacturing of molding compounds and moldings The composition according to the invention can be used to produce thermoplastic molding compounds.The thermoplastic molding compounds according to the invention can be produced, for example, by mixing the individual components of the composition in a well-known manner and melt compounding and melt extrusion, preferably at temperatures between 200°C and 320°C, particularly preferably between 240°C and 310°C, very particularly preferably between 260°C and 300°C, in customary equipment, such as internal mixers, extruders and twin-screw extruders.In the present application, this process is generally referred to as compounding.
[0123] The term "moulding compound" should therefore be understood to mean the product obtained by melt compounding and melt extruding the constituents of the composition.
[0124] The mixing of the individual components of the composition can be carried out in a known manner, either sequentially or simultaneously, either at a temperature of about 20° C. (room temperature) or higher. This means, for example, that some components can be metered in through the main intake of an extruder, while the remaining components can be introduced later in the compounding process through a side extruder.
[0125] The molding compound according to the invention can be used to produce any type of molding and semi-finished product.These can be produced, for example, by injection molding, extrusion and blow molding processes.Another form of processing is the production of moldings by thermoforming from previously produced sheets or films.The molding compound according to the invention is particularly suitable for processing by extrusion, blow molding and thermoforming processes.
[0126] An example of a semi-finished product is a sheet.
[0127] It is also possible to meter the constituents of the composition directly into an injection molding machine or into an extrusion unit and process them to give moldings.
[0128] Examples of such moldings which can be produced from the compositions and molding compounds according to the invention are films, profiles, housing parts of any kind for office equipment such as monitors, flat screens, notebooks, printers, copiers, etc.; sheets, pipes, electrical equipment ducts, windows, doors and other profiles for the construction sector, as well as electrical and electronic components such as switches, plugs and sockets, and parts for vehicles, in particular for the automotive sector. The compositions and molding compounds according to the invention are also suitable for the production of the following moldings or articles: interior equipment parts for rail vehicles, ships, aircraft, buses and other mobile vehicles, body components for mobile vehicles, housings for electrical equipment, including mini-transformers, housings for equipment for processing and transmitting information, housings and upholstery for medical equipment, massage equipment and its housing, children's ride-on toys, sheet-like wall elements, housings for safety equipment, thermally insulated transport containers, moldings for sanitary and bathroom equipment, protective grilles for ventilation openings, and housings for gardening equipment.
[0129] The present invention further relates to moldings, preferably sheet-like moldings such as sheets, and vehicle body parts such as mirror housings, fenders, spoilers, bonnets, etc., produced from the above-mentioned compositions.
[0130] The moldings can be small or large and can be used for exterior or interior applications. It is preferred to produce large moldings for vehicle construction, especially for the automotive field. The molding compounds according to the invention can be used, inter alia, to produce exterior body parts, such as fenders, trunk lids, engine bonnets, bumpers, luggage compartments, luggage compartment covers, vehicle roofs or other body accessories.
[0131] Moldings or semi-finished products made from the molding compounds / compositions according to the invention can also be placed in composites with further materials, for example metals or plastics. After optional painting, for example of exterior body parts, a paint layer can be placed directly on the molding compounds according to the invention and / or on the materials used in the composite. The molding compounds according to the invention and moldings / semi-finished products made from the molding compounds according to the invention can be used to manufacture finished parts, such as exterior body parts, in composites with other materials or by themselves, by customary techniques for bonding and joining several components or parts, such as coextrusion, film insert molding, overmolding of inserts, adhesive bonding, welding, screwing or clamping, etc.
[0132] Further embodiments 1 to 40 of the present invention are described below:
[0133] 1. A composition for producing a thermoplastic molding compound, comprising the following components: A) at least one polymer selected from the group consisting of polycarbonates and polyester carbonates; B) at least one polyester; C) phosphorous acid; D) at least one phosphonite; E) at least one sterically hindered phenol; A composition comprising:
[0134] 2. Component A is an aromatic polycarbonate having a weight average molecular weight M of 22 kg / mol to 28 kg / mol, determined by gel permeation chromatography in methylene chloride using a polycarbonate based on bisphenol A as standard. w 2. The composition of embodiment 1, comprising:
[0135] 3. The composition according to any one of the preceding claims, wherein component A is an aromatic polycarbonate based on bisphenol A.
[0136] 4. The composition according to any of the above embodiments, characterized in that component B contains structural units derived from terephthalic acid and up to 50 mol % of structural units derived from phthalic acid, isophthalic acid, naphthalene-2,6-dicarboxylic acid, 4,4'-diphenyldicarboxylic acid, succinic acid, adipic acid, and cyclohexanedicarboxylic acid.
[0137] 5. A composition according to any of the above embodiments, characterized in that component B does not contain structural units of acids other than terephthalic acid and isophthalic acid.
[0138] 6. A composition according to any of the above embodiments, characterized in that component B does not contain structural units of acids other than terephthalic acid.
[0139] 7. The composition according to any of the above embodiments, characterized in that component B contains structural units derived from ethylene glycol, butane-1,4-diol, propanediol, cyclohexane-1,4-dimethanol, tetramethylcyclobutanediol and isosorbitol.
[0140] 8. A composition according to any of the above embodiments, characterized in that component B is selected from the group consisting of polyethylene terephthalate and polybutylene terephthalate.
[0141] 9. The composition according to any of the above embodiments, characterized in that as component B, a polyethylene terephthalate having an intrinsic viscosity of 0.52 dl / g to 0.95 dl / g is used.
[0142] 10. The composition according to any of the above embodiments, characterized in that as component B, a polyethylene terephthalate having an intrinsic viscosity of 0.56 dl / g to 0.80 dl / g is used.
[0143] 11. A composition according to any of the above embodiments, characterized in that as component B, a polyethylene terephthalate having an intrinsic viscosity of 0.58 dl / g to 0.68 dl / g is used.
[0144] 12. The composition of any of the above embodiments, 40% to 80% by weight of component A; 15% to 45% by weight of component B; 0.005% by weight to 0.1% by weight of component C; 0.05% to 1% by weight of component D; 0.05% by weight to 1% by weight of component E; F) 0% to 25% by weight of a talc-based mineral filler; G) 0% to 20% by weight of at least one additive selected from the group consisting of lubricants and release agents, flame retardants, flame retardant synergists, conductive additives, UV / light protectants, nucleating agents, hydrolysis protectants, scratch resistance improving additives, IR absorbers, optical brighteners, fluorescent additives, impact modifiers, dyes and pigments, and fillers and reinforcing agents other than component F; A composition comprising:
[0145] 13. The composition according to any of the above embodiments, characterized in that the proportion of component A in the composition is 40% by weight to 80% by weight, more preferably 45% by weight to 75% by weight, and particularly preferably 50% by weight to 66% by weight.
[0146] 14. The composition according to any of the above embodiments, characterized in that the proportion of component B in the composition is 15% by weight to 45% by weight, more preferably 18% by weight to 40% by weight, and particularly preferably 20% by weight to 35% by weight.
[0147] 15. A composition according to any of the above embodiments, characterized in that the proportion of component C in the composition is 0.005% by weight to 0.1% by weight, more preferably 0.008% by weight to 0.06% by weight, and particularly preferably 0.01% by weight to 0.05% by weight.
[0148] 16. A composition according to any of the above embodiments, characterized in that the proportion of component D in the composition is 0.05% by weight to 1% by weight, more preferably 0.08% by weight to 0.8% by weight, and particularly preferably 0.1% by weight to 0.3% by weight.
[0149] 17. A composition according to any of the above embodiments, characterized in that the proportion of component E in the composition is 0.05% by weight to 1% by weight, preferably 0.08% by weight to 0.8% by weight, and more preferably 0.1% by weight to 0.3% by weight.
[0150] 18. A composition according to any of the above embodiments, characterized in that the proportion of component F in the composition is 0% by weight to 25% by weight, more preferably 0% by weight to 20% by weight, and particularly preferably 5% by weight to 20% by weight.
[0151] 19. A composition according to any of the above embodiments, characterized in that the proportion of component G in the composition is 0% by weight to 20% by weight, more preferably 0.1% by weight to 15% by weight, and particularly preferably 0.2% by weight to 10% by weight.
[0152] 20. The composition according to any of the above embodiments, 50% to 66% by weight of component A; 20% to 35% by weight of component B; 0.01% to 0.05% by weight of component C; 0.1% to 0.3% by weight of component D; 0.1% by weight to 0.3% by weight of component E; 5% to 20% by weight of component F; 0.2% by weight to 10% by weight of component G; A composition comprising:
[0153] 21. A composition according to any of the previous embodiments, characterized in that component C is used as a solid.
[0154] 22. A composition according to any of the previous embodiments, characterized in that component C is used in combination with an organic or inorganic adsorbent or absorbent.
[0155] 23. The composition according to embodiment 20, characterized in that component C is used bound to silica.
[0156] 24. As component D, structure (5): [ka] A composition according to any of the above embodiments, characterized in that a compound according to is used.
[0157] 25. Component E has structures (8) and (9): [ka] The composition according to any of the above embodiments, characterized in that it is selected from at least one compound according to
[0158] 26. A composition according to any of the above embodiments, characterized in that as component F, talc having an Al2O3 content of less than 0.7% by weight is used.
[0159] 27. Component F has an upper particle size d of less than 6 μm 95 3. The composition of any of the above embodiments, comprising:
[0160] 28. The composition of any of the above embodiments, which does not include any fillers or reinforcing agents other than component F.
[0161] 29. A composition according to any of the above embodiments, wherein the composition does not contain a rubber-modified graft polymer.
[0162] 30. A composition according to any of the previous embodiments, characterized in that the composition does not contain a vinyl (co)polymer.
[0163] 31. A composition according to any of the above embodiments, wherein the composition does not contain a styrene-acrylonitrile copolymer.
[0164] 32. The composition according to any of the above embodiments, wherein the composition does not contain a phosphorus-based flame retardant.
[0165] 33. A composition according to any of the previous embodiments, characterized in that the composition does not contain carbon fibers.
[0166] The composition according to any one of the above embodiments, wherein about 34.90% by weight of the composition is made up of components A to G.
[0167] The composition according to any one of the above embodiments, wherein about 35.95% by weight of the composition is made up of components A to G.
[0168] 36. A composition according to any one of the above embodiments, consisting of components A to G.
[0169] 37. A process for producing a molding compound, characterized in that the components of the composition according to any one of embodiments 1 to 36 are mixed with each other at a temperature between 200°C and 320°C, followed by cooling and pelletizing.
[0170] 38. A molding compound obtainable by the process according to embodiment 37.
[0171] 39. Use of the composition according to any of the embodiments 1 to 36 or of the molding compound according to embodiment 37 for producing a molded body.
[0172] 40. A molded body obtainable from the composition according to any one of embodiments 1 to 36 or from the molding compound according to embodiment 38. EXAMPLES
[0173] Ingredient A-1 Molecular weight of 24 kg / mol (weight average M w, as measured by GPC (gel permeation chromatography) using bisphenol A-based polycarbonate standards.
[0174] Ingredient A-2 Molecular weight of 28 kg / mol (weight average M w , as measured by GPC (gel permeation chromatography) using bisphenol A-based polycarbonate standards.
[0175] Ingredient B-1 Polyethylene terephthalate (e.g. PET from Invista, Germany) with an intrinsic viscosity of 0.623 dl / g. The specific viscosity is measured in dichloroacetic acid at 25° C. and a concentration of 1% by weight. The intrinsic viscosity is calculated from the specific viscosity by the following formula: Intrinsic viscosity=specific viscosity×0.0006907+0.063096
[0176] Ingredient B-2 Polyethylene terephthalate (e.g. PET from Invista, Germany) with an intrinsic viscosity of 0.664 dl / g. The specific viscosity is measured in dichloroacetic acid at 25° C. and a concentration of 1% by weight. The intrinsic viscosity is calculated from the specific viscosity by the following formula: Intrinsic viscosity=specific viscosity×0.0006907+0.063096
[0177] Component C-1 Phosphorous acid, H3PO3, as a solid, Sigma-Aldrich Chemie GmbH (Germany)
[0178] Component C-2 (comparison) Zn(H2PO4)2, Budit (trademark) T21, Budenheim (Germany)
[0179] Component D-1 Dimeric phosphonite according to structure (5), tetrakis(2,4-di-tert-butylphenyl)-1,1-biphenyl-4,4'-diylbisphosphonite, Irgafos™ P-EPQ, BASF (Germany) [ka]
[0180] Ingredient D-2 (comparison): Phosphite stabilizer according to structure (10), Irgafos™ 168, tris(2,4-di-tert-butyl-phenyl)phosphite; BASF (Germany) [ka]
[0181] Component E-1 Sterically hindered phenol according to structure (8), Irganox™ 1010, pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), BASF (Germany) [ka]
[0182] Component E-2 Sterically hindered phenol according to structure (9), Irganox™ 1076, octadecyl 3-[3,5-di-tert-butyl-4-hydroxyphenyl]propionate, BASF (Germany) [ka]
[0183] Component F Mean particle diameter d of 1.2 μm measured using a sedigraph 50 and d of 3.5 μm 95 and a talc having an Al2O3 content of 0.5 wt. %, Jetfine™ 3CA from Imerys Talc, Austria.
[0184] Ingredient G-1 Pentaerythritol tetrastearate as a release agent, Cognis Oleochemicals GmbH (Germany)
[0185] Ingredient G-2 Montan Acid Ester Wax (Licowax™ E) as a Lubricant / Mold Release Agent
[0186] Ingredient G-3 Carbon black, Black Pearls™ 800, Cabot
[0187] Manufacturing of molding compounds A molding compound according to the invention containing components A to E is produced in a ZSK25 twin screw extruder from Coperion, Werner and Pfleiderer (Germany) at a melt temperature of 270°C.
[0188] Preparation and testing of test specimens Pellets from each compound were processed into test specimens in an injection molding machine (eg, Arburg) at a melt temperature of 270°C and a mold temperature of 70°C.
[0189] The heat distortion resistance was determined on unilaterally injected test bars with dimensions 80 mm x 10 mm x 4 mm, produced at 270°C and a dwell time of 43 seconds, according to DIN ISO 306 (Vicat softening temperature, method B with a load of 50 N and a heating rate of 120 K / h, edition from 2013). Furthermore, the Vicat softening temperature was determined on test bars produced at 300°C and a dwell time of 129 seconds. The difference ΔVicat = Vicat (test bars at 270°C and a dwell time of 43 seconds) - Vicat (test bars at 300°C and a dwell time of 129 seconds) is taken as a measure of the heat load capacity.
[0190] The impact strength is determined according to ISO 180 / 1U (1982 edition) by ten measurements on test bars having dimensions of 80 mm×10 mm×4 mm at room temperature (23° C.).
[0191] The glass transition temperature (T g PC), polyester melting temperature (T m PET) and polyester crystallization temperature (T c The thermal properties of the PET (PET) were measured using differential scanning calorimetry (DSC) according to ISO 11357-3:2018: the temperature and the enthalpy of melting and crystallization were determined using a Mettler DSC 3+ instrument. The measurements were carried out in a nitrogen atmosphere (50 ml N2 / min) with a heating rate of 10 K / min in the temperature range from -40 °C to 320 °C. In this case, heating and cooling were repeated several times. g was determined in each case as the midpoint of the glass transition during the second heating and the first cooling. m is determined as the peak temperature during the second heating, and T c was determined as the peak temperature during the first cooling.
[0192] The unstable phase behavior / thermal damage of the investigated materials led to the melting temperature (T m PET) and / or polyester crystallization temperature (T c If it was not possible to determine the level of PET, the result should be recorded as "not measurable."
[0193] The following examples serve to further illustrate the invention.
[0194] [Table 1]
[0195] [Table 2]
[0196] [Table 3]
[0197] Table 1 shows that the composition according to the invention comprising components C, D and E allows the production of moulded bodies with only a small drop in heat distortion temperature (ΔVicat) after high thermal stress, combined with improved impact strength. Furthermore, DSC studies show that the transition temperatures of the polycarbonate and polyester components are at high levels both during multiple heating and repeated cooling, so that it can be assumed that phase separation and phase stability are well preserved.
[0198] Without component C (C1), the heat distortion temperature drops significantly under high thermal stress and the polycarbonate and polyester components are undesirably mixed. Increasing the addition of component D cannot compensate for the absence of component C.
[0199] In particular, when component D is a phosphite rather than a phosphonite (C6, C7 and C8), the resilience is not at the desired level.
[0200] When an acid phosphate is used as component C (C9), the resilience also decreases and the transition temperature decreases.
[0201] If only component C according to the invention is used, and components D and E are absent, the transition temperature decreases for the same amount of component C (Example 4 compared to C10). This cannot be compensated for by using a higher amount of component C, since this would result in a significant decrease in impact strength (C12).
[0202] The advantage of combining components C, D and E is also evident in compositions without mineral filler (Table 2).
Claims
1. A composition for producing a thermoplastic molding compound, comprising the following components: A) at least one polymer selected from the group consisting of polycarbonates and polyestercarbonates; B) at least one polyester; C) phosphorous acid; D) at least one phosphonite; E) at least one sterically hindered phenol; A composition comprising:
2. The component A is an aromatic polycarbonate having a weight average molecular weight M of 22 kg / mol to 28 kg / mol, determined by gel permeation chromatography in methylene chloride using a polycarbonate based on bisphenol A as standard. w The composition of claim 1 having
3. 3. The composition according to claim 1, wherein as component B a polyethylene terephthalate is used having an intrinsic viscosity of 0.58 dl / g to 0.68 dl / g.
4. 40% to 80% by weight of component A; 15% to 45% by weight of component B; 0.005% to 0.1% by weight of component C; 0.05% to 1% by weight of component D; 0.05% to 1% by weight of component E; F) 0% to 25% by weight of a talc-based mineral filler; G) 0% to 20% by weight of at least one additive selected from the group consisting of lubricants and release agents, flame retardants, flame retardant synergists, conductive additives, UV / light protectants, nucleating agents, hydrolysis protectants, scratch resistance improving additives, IR absorbers, optical brighteners, fluorescent additives, impact modifiers, dyes and pigments, and fillers and reinforcing agents other than component F; The composition according to any one of claims 1 to 3, comprising:
5. 5. The composition according to claim 1, wherein component C is used as a solid.
6. The composition according to any one of claims 1 to 5, characterized in that the proportion of component C in the composition is from 0.01% by weight to 0.05% by weight.
7. As component D, the structure (5): 【Chemistry 1】 7. Composition according to claim 1, characterized in that a compound according to the formula:
8. Component F has an upper particle size d of less than 6 μm 95 The composition according to any one of claims 1 to 7, characterized in that it has
9. The composition according to any one of claims 1 to 8, consisting essentially of components A to G.